Alternative Conceptions of Feedback in Dynamic Decision Environments: An Experimental Investigation - Sengupta, Kishore; Abdel-Hamid, Tarek K. (Management Science, 1993)
Studies conducted in recent years have shown that outcome feedback in dynamic decision-making tasks does not lead to improved performance. This has led researchers to examine alternatives to outcome feedback for improving decision makers' performance in such tasks. This study examines the feasibility of improving performance in dynamic tasks by providing cognitive feedback or feedforward. We report a laboratory experiment in which subjects managed a set of simulated software development projects. Results indicate that subjects provided with cognitive feedback performed best, followed by those provided with feedforward. Subjects provided with outcome feedback performed poorly. We discuss the implications of the results for decision support in dynamic tasks.